Proses Bermukim dan Pemenuhan Fasilitas Permukiman Kelurahan Ngemplak Simongan Kecamatan Semarang Barat Kota Semarang - Anggraini Aulia Niken; Hariyanto Hariyanto (Geo-Image, 2018)
This study aims to find out the settlement process of the Ngemplak Simongan Urban Village, as well as choosing to live in Simongan. The population in this research is Ngemplak Simongan urban village and sampling technique used is simple sampling method. Methods of data collection include: observation, interview, and questionnaire. The results of the research are: 1) The settlement process that occurred in the Simongan community that is relocation from the government, arises the invitation to live, and continues with the descendants who occupy the land. 2) Reasons for choosing to reside in Simongan that is having inherited land, close to work place, price tanag cheap. 3) Fulfillment of majority electricity facilities using new power lines, clean water supply with artesian and PAM wells, and road conditions have a wide variety of types, widths and slopes.